Prevalence of non-communicable diseases and their risk factors at a semi-urban community, Pakistan - Sajida Naseem; Umme Kulsoom Khattak; Haider Ghazanfar; Awais Irfan (The Pan African Medical Journal, 2016)

(untitled)
INTRODUCTION: Pakistan is currently facing the double burden of communicable (38%) and non- communicable diseases (49%) according to WHO NCD Country Profiles 2014. About 50% of all deaths are attributed to NCD's. The objective of this study was to determine the burden of non-communicable diseases in semi urban community of Islamabad. METHODS: we carried a cross sectional study to estimate the burden of non-communicable diseases in an urban setting, a community based cross sectional survey covering 1210 households was carried out over a period of three months. Households were selected through consecutive non-probability sampling, among which adult females and males who were permanent resident of the community were interviewed through a structured questionnaire in urdu language. SPSS version 21 was used to analyze the data. Descriptive statistics were calculated. RESULTS: about 38.7% individuals had High BP / IHD, 34.4% had oro-dental health problems, 24.3% were physically disabled and 14.6% had diabetes. Among the risk factors, 48.2% were tobacco user, 13.60% were drug abuser and 1.8% alcoholics. CONCLUSION: we conclude that the prevalence of non-communicable diseases is quite high in the above setting as compared to the National indicators, which demands timely intervention to curtail the existing burden of NCD.